The Method of Writing Music Ornaments in an Old Kurdish Music notes, in Iraqi Kurdistan - Hazhar Ahmed Mustafa; Kawan Ahmad Elias (Zanco Journal of Humanity Sciences)
This effort is a description and analysis of how musical elements were written in ancient Kurdish musical notes, especially in the Erbil art group and the music groups in Sulaymaniyah and Dohuk.The uncertainty in this topic motivated the conduct of this research. Because most of the available notes are devoid of these ornament symbols, and yet they are played through listening, they are full of ornament symbols... Therefore, this situation raised a number of questions for researchers; the search for answers to these questions became the basis of this research... in order to solve a topic Ornament between Kurdish music and songs, as it constitutes the objective of this study. For this purpose, data such as production notes sounds of songs, cassettes, and manuscripts of these orchestras were collected, and due to the lack of written sources, the sources were collected through personal interviews with members and musicians of these groups, to know how the ointment is reflected in Kurdish music.